THINKING OF FAZLUR RAHMAN ABOUT ISLAMIC EDUCATION - mirawati mirawati (Al-Manar : English and Arabic Journal, 2014)
Fazlur Rahman is one of the new innovator in Islam that has a big influence in 20 century, especially in Pakistan, Malaysia, Indonesia, and other countries (Islamic countries), and the Chicago America (West country) that has the various thinking related with the problem. He success thinking critically either Islam or West tradition. He successes to develop a method that can give alternative solution toward contemporary Muslim. Fazlurrahman offers the idea that neo-modernism, it is certainly included in the educational aspect. Education surrounding the neo-modernism have two models; traditional and modern. Both of these models have different character. In one side follow toward old model while the second want to rebuilt the new version in education. In otherwise, both of them have the same objectives to empower people (empowerment). The differences only in matter of technical and operational methods. According to Rahman, the goal of Islamic education is formatted to realize Muslim that civilized order and consistent to God.